CORONAVIRUS DISEASE 2019, DENGUE HEMORRHAGIC FEVER, AND THE CLINICAL SIMILARITY - SURYANA, KETUT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Recently, coronavirus disease-19 (COVID-19) case is increasing in Indonesia, simultaneously with the outbreak of dengue hemorrhagic fever (DHF). DHF is generally observed to rise at the beginning of the year that peaks between March and April due to the rainy season and high temperatures. The outbreak of COVID-19 started in Wuhan, China, since December 2019, and it has spread quickly worldwide as a pandemic. COVID-19 and DHF have had comparable clinical indication, laboratory highlights, and it has serious implications for the patients as well as for the general health. Therefore, to distinguish, all the doctors in the primary health care have to be aware and to work carefully.